GR_GERICHTE U 2019 77 vom 12. August 2021 , 4A_489/2021 vom 11.10.2021 - GR Gerichte (2021)
concessione (riversione e indennizzo per la rete di distribuzione comunale) - PVG 2021 Nr. 23 | Konzessionen